Index Analysis of Administrative Offenses in Ukraine in 2014-2018 - Kulynych R. О. (Statistics of Ukraine, 2020)
An objective assessment of the state and development of socio-economic phenomena and processes can only be ensured by use of properly selected statistical and mathematical methods. These methods cease to be a matter of interest in practical activities where there is no certainty as to how far they can be applied to specific tasks. Given significant advances in technology for the collection and processing of statistics, the proper use of statistical and mathematical methods is significantly hampered by insufficient knowledge of methods, their specifics, applications, and capacities to evaluate information. The article deals with the methodology of index analysis of statistical information on administrative offenses using data in Ukraine for 2014–2018. It is shown that the analytical system of statistical indices can be used to solve the tasks set out in the article, by the method of statistical groupings using the methods of statistical analysis of structural shifts. The theoretical and methodological provisions of the index analysis of statistical information on administrative offenses are demonstrated by data on the amount of the fines imposed, the amount of the fine paid voluntarily and the amount of property damage caused. The statistical information on the dynamics of fines and property damages in Ukraine for 2014–2018, as well as information on the fining depending on the performance of the administrative bodies, including by legal ground for the fining, are provided. The hypothesis on the inadequate quality of the administrative records prepared by the respective authorities needs to be further investigated, as the voluntary payments of fines, case-law of the local courts or compensation for material damage tend to be low. Considering the above hypothesis, it is established that an increase in the amount of fines imposed is attributed to the numbers of administrative cases rather than the quality of information used in their preparation.